PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT ERA MULIA ABADI SEJAHTERA - Rizka Anggraeni Amaliyanti; Pompong Budi Setiadi; Sri Rahayu (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the effect of work motivation and work environment on employee performance. This research was conducted on employees at PT Era Mulia Abadi Sejahtera in Malang, East Java. The research method used in this research is descriptive by using quantitative methods. This study uses primary data, namely the distribution of questionnaires by taking employee respondents at PT Era Mulia Abadi Sejahtera in Malang, East Java. This study uses a sample of the total population of the number of employees in the office. The analytical method used is multiple regression analysis which is processed using the SPSS application. The results of this study indicate that the variables of work motivation and work environment have a positive effect on employee performance. And the variables of work motivation and work environment simultaneously affect employee performance.